On Nirenberg-type conditions for higher-order systems on time scales - Amster, P. (2008)
We study the existence of periodic solutions for a nonlinear system of nth-order differential equations on time scales. Assuming a suitable Nirenberg-type condition, we prove the existence of at least one solution of the problem using Mawhin's coincidence degree. © 2007 Elsevier Ltd. All rights reserved.